Causes of overweight and obesity in children and adolescents - Maślak, Agnieszka Danuta; Kusz, Monika; Pawluczuk, Paulina; Alzubedi, Adam; Polski, Paweł (Journal of Education, Health and Sport, 2020)
Obesity is caused by positive energy balance. Excessive body weight in children is classified by using charts for body mass index (BMI). The prevalence of overweight and obesity is a growing public health problem worldwide. Excess body fat may lead to serious health problems in later life, so it is important to know the main reasons causing weight gain. Those could be classified as genetic and non-genetic factors. The second ones include medical problems (e.g. endocrine and neurological diseases), family and social impact, environmental influence, bad eating habits, sedentary lifestyle, cultural factors. There are two most important phases in life such as infancy and puberty, which may determine development of overweight or obesity. It is crucial to pay special attention on those periods to prevent weight gain development.